Behavior of the interaction between twin transitional round fountains in a homogeneous fluid, Part 1: Experimental study. (July 2015) - Mahmud, Hasan; Lin, Wenxian; Gao, Wenfeng; Hill, Blair; Armfield, S.W.; He, Yinghe
Abstract: The interaction of multiple sourced fountains is very common in many applications such as computers and electronic instruments, discharge of waste water from power plants to marine environments, displacement ventilation and air conditioning of large building spaces. But the understanding of such an interaction is currently scarce. This paper is the first part of the study on the behavior of the interaction between twin transitional round fountains with equal power in a homogeneous fluid. In this paper, the interaction behavior is investigated experimentally using a noninvasive PIV technique and flow visualization over the ranges 25 ⩽ Re ⩽ 400 and 1 ⩽ Fr ⩽ 5 at the fixed spacing of D / X 0 = 10, where Re and Fr are the Reynolds and Froude numbers, D is the spacing between the two fountain sources, and X 0 is the radius of orifices at the fountain source. The interaction behavior is observed to be dominated by bobbing and flapping motions and is either steady, or unsteady and weakly multi-modal or strongly multi-modal, depending on the specific values of Re and Fr . In a steady interaction, the bobbing–flapping motions are only present in its initial development stage and the interaction will attain a steady state in the later development stage in which the bobbing–flapping motions are no longer present and the maximum interaction height, z i, becomes constant. In an unsteady interaction, the interaction remains unsteady all the time and the bobbing–flapping motions are present at all development stages. The unsteady interaction is characterized by a finite number of discrete modes, with the time averaged z i approximately constant. Among all cases considered, the steady interaction behavior is observed for the cases of Re ⩽ 100 with all Fr values considered and of Fr ⩽ 1 with all Re values considered, except Re = 400 ; the unsteady weakly multi-modal interaction behavior is observed for 150 ⩽ Re ⩽ 300 with 1.5 ⩽ Fr ⩽ 5 and Fr = 1 with Re = 400 ; and the unsteady strongly multi-modal interaction behavior is found for Re = 400 with 1 < Fr ⩽ 5 . Dimensional analysis and the experimental results are also used to develop an empirical scaling relation between z ¯ i, which is the time-averaged dimensionless maximum interaction height at full development, and Re and Fr, i.e., z ¯ i = 0.194 Fr 7 / 4 Re 1 / 4 over the ranges 25 ⩽ Re ⩽ 400 and 1 ⩽ Fr ⩽ 5, at the fixed spacing of D / X 0 = 10 .